Recent Advances in Electrochemical Water Splitting and Reduction of CO2 into Green Fuels on 2D Phosphorene‐Based Catalyst. Issue 1 (8th December 2020) - Srivastava, Rohit; Nouseen, Shaista; Chattopadhyay, Jayeeta; Woi, Pei Meng; Son, Do Ngoc; Bastakoti, Bishnu Prasad
Abstract : Recently, monolayer or few‐layered phosphorene nanosheets and other phosphorene‐based materials have gained huge attention due to their unique semiconducting and optical properties. But there is a huge unexplored area of research where phosphorene‐based catalysts could find new applications. Among these are the urgency of making new functionalized phosphorene materials and studying their catalytic (including photo and electrocatalytic) activities in various types of reactions. Phosphorene has a wide range of emerging applications in the field of energy conversion and storage, photovoltaic devices, and biomedical applications. However, the application of 2D phosphorene‐based catalyst in the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), reduction of CO2 into green fuels, and the nitrogen electroreduction reaction (N2 RR) have not been explored further. Herein, state‐of‐the‐art synthetic strategies of 2D phosphorene produced from allotropes of black phosphorus with their significant role as nanocatalysts in the HER, OER, hydrogen storage, electrochemical reduction of CO2 into valuable green fuels, and the N2 RR are focused on. This review provides a wide range of knowledge on the current scenario to the researcher, scientist, industrialist, and professional working in the field of material research for energy applications. Abstract : Black phosphorous and phosphorene‐based materials are an emerging field of research due to unique semi‐conducting and optical properties. The review focuses on state‐of‐the‐art synthetic strategies of 2D phosphorene‐based catalysts in the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), hydrogen storage, electrochemical reduction of CO2 into valuable green fuels, and nitrogen electroreduction reaction (N2 RR).